2015
DOI: 10.1177/1468018115594650
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking ‘women’s health’ in the context of PPPs: A return to instrumentalism in development policy and practice?

Abstract: There has been a significant increase in funding for health programmes in development over the last two decades, partly due to the formation of public–private partnerships. This article examines the impact of public–private partnerships from the perspective of women’s health, asks whether the current culture of funding has led to an increased instrumentalism in women’s health programming and what effects this has on how women’s health is addressed at the level of practice. The article is based on research carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…This in turn impacts on the types of projects that NGOs are able to promote and engage with, which often serves to reinforce more limited understandings of women's health and fails to give voice to the women they claim to be supporting (Gideon and Porter, 2015). Research conducted with UK-based NGOs working on women's health programmes has highlighted how the dominant discourse emerging from corporate sector actors is reducing the understanding of women's health to more instrumentalized notions of maternal and reproductive health.…”
Section: The Limits Of Indicators For Understanding Gendered Inequalimentioning
confidence: 99%
See 3 more Smart Citations
“…This in turn impacts on the types of projects that NGOs are able to promote and engage with, which often serves to reinforce more limited understandings of women's health and fails to give voice to the women they claim to be supporting (Gideon and Porter, 2015). Research conducted with UK-based NGOs working on women's health programmes has highlighted how the dominant discourse emerging from corporate sector actors is reducing the understanding of women's health to more instrumentalized notions of maternal and reproductive health.…”
Section: The Limits Of Indicators For Understanding Gendered Inequalimentioning
confidence: 99%
“…A study of UK-based NGOs working in the health sector found that these shared ideas appear to privilege the market-led needs of distributing products or services, rather than utilizing the knowledge and experience of NGOs derived from working with those at 'the grassroots'. However, they did not want to use this power to fundamentally challenge their new funding partners to address more deeply embedded inequalities in health (Gideon and Porter, 2015). Some (large, international) NGOs do have significant power, based on the value of their 'brand', and for respondents in these NGOs this power makes the relationship with some private sector partners more equal, or at least more nuanced in the way power is balanced.…”
Section: 'Perverse Outcomes' On the Ground: Ngos Hiv/aids And Maternmentioning
confidence: 99%
See 2 more Smart Citations
“…These multiple actors and their vertical orientations have led to pressing gender equity concerns and a shift away from a focus on the economic, political, social, and commercial determinants of health. 78 This shift should prompt closer attention to the unintended gendered effects of global health programmes.…”
mentioning
confidence: 99%